2011
DOI: 10.1111/j.1526-4610.2011.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Treatment of Headaches in Veterans With Mild Traumatic Brain Injury

Abstract: There was an increased prevalence of headaches in veterans with mild TBI. Most of the TBI veterans in our study group were exposed to blast injury and findings indicate that the nature of head trauma may be contributing to headaches. Findings highlight the need for developing effective headache prevention and treatment strategies for all persons with mild TBI and in particular for veterans with blast-related mild TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
2
47
1
Order By: Relevance
“…42,43 TRPV1 antagonists have also been evaluated in the treatment of this disorder 44 . Of direct relevance to our research, a significant percentage of military veterans with blast-related injuries and confirmed TBI have also been diagnosed with migraine headaches and/or chronic, daily headaches 45 . Inflammatory cytokines are known to play a significant role in trigeminal nerve sensitization regulation in migraines.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 TRPV1 antagonists have also been evaluated in the treatment of this disorder 44 . Of direct relevance to our research, a significant percentage of military veterans with blast-related injuries and confirmed TBI have also been diagnosed with migraine headaches and/or chronic, daily headaches 45 . Inflammatory cytokines are known to play a significant role in trigeminal nerve sensitization regulation in migraines.…”
Section: Discussionmentioning
confidence: 99%
“…10 We suspect that the duration of the time window in part reflected a concern that a longer window would increase the number of people who would claim to have PTH for secondary gain including medicolegal issues. 1,3,20,21,50,52,79,80,[88][89][90]154,155 Longitudinal imaging studies demonstrate evolving brain changes occurring over years following TBI. 90 We suggest the longer time window in order to include people whom we observed developed headaches more than 7 days after TBI (see sections on PTH in civilians and military PTH).…”
Section: Box 6-relationship Of Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…PTH is more frequent after mild TBI (mTBI) compared with moderate or severe TBI 2 and can resemble one or more primary headache disorders 39 . The most common PTH patterns resemble two primary headache disorders—migraine or probable migraine and tension-type headaches—and migraine-type headaches are more prevalent 35, 8, 10, 11 . In one prospective study of adult civilian TBI associated with motor vehicle accidents, 58% of subjects continued to have PTH one year after their TBI 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In one prospective study of adult civilian TBI associated with motor vehicle accidents, 58% of subjects continued to have PTH one year after their TBI 12 . Migraine-like PTHs usually resemble migraine without aura 5, 7, 8, 13, 14 . Neck injury in conjunction with TBI can result in cervicogenic headaches or pain that may resemble occipital neuralgia 11, 15 .…”
Section: Introductionmentioning
confidence: 99%